The Determinants and Role of Personal Agency in the Self-Regulation Empowerment Program (SREP): Influence of Social Cognitive Theory - Cleary, Timothy J. (Educação: Teoria e Prática, 2025)
Albert Bandura is one of the most prolific and influential psychologists and researchers in history. In addition to championing the importance of people’s perceptions of personal capability (i.e., self-efficacy), Bandura developed a complex, generative perspective of personality (i.e., Social Cognitive Theory [SCT]) that emphasizes the potential of humans to act with purpose, intentionality, and agency on the world in which they operate. In this paper, I review core principles and mechanisms embedded within SCT that stimulate and cultivate this notion of personal agency, such as self-efficacy, cyclical regulation, triadic reciprocality, and observational learning. I then discuss how these agency-enhancing principles were used to develop the procedures and activities of an applied academic intervention program designed to optimize middle school and high school student motivation, self-regulated learning, and academic achievement. By mapping Bandura’s core principles to the activities of a school-based intervention, I hope to shine the light on how educators and school-based practitioners can similarly apply SCT principles in their professional roles.